Simulation of Temperature Changes in the western half of Iran during (1960-2100) by using reanalysis datasets and RCP8.5 Models - Hossin Asakereh; Piero Lionello; hossein mirmousavi; sahar sadrafshari (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this research is to identify changes in the temperature trend in the western half of Iran. For this purpose, monthly temperature data of 15 synoptic stations were collected during 1960-2010. Quality control was applied on these data by applying Pettit, SNHT, Buishand and Von Neumann’s tests. Later data Simulated and compared with reanalysis data such as ERA-Interim, ERA-20C, NCEP and CMIP5 models (RCP8.5 for the period 1960-2100). Trends were calculated by the Mean Kendall test and the Sen’s estimator (95 % confidence level). Based on the results obtained from all models, a significant positive trend was observed in spring, summer and autumn, and only in winter according to ERA-Interim. Based on CMIP5 results for the period 2050-2100 values between 2 and 4 ° C/100 achieved, which is lower than the results of other models for the period 1979-2010. Considering the CMIP5 models and their overall average in the study area, an increase in annual temperature (7 ° C /100) for the second half of the 21st century was confirmed.